Examining the Impact of COVID-19 on Early Intervention Service Provision for Military Families: A Brief Report - Zellner, Matthew A.; Grauzer, Jeffrey; Kaat, Aaron J.; Roberts, Megan Y. (Journal of early intervention, 2025)
Understanding the extent to which the COVID-19 pandemic disrupted birth-to-three early intervention (EI) service provision is critical as these services play an essential role in ensuring positive long-term developmental outcomes for children with disabilities, including those who are military dependents. The present study leveraged an interrupted time series approach to compare monthly service provision rates before and after the onset of the pandemic for a subset of children served by the Army Medical Department’s Educational and Developmental Intervention Services EI program. Analysis identified 77% and 93% immediate step decreases in EI referral and enrollment rates, respectively, following the onset of the pandemic in March 2020; however, rates returned to, or exceeded, prepandemic levels by late 2020. There were limited differences by race or ethnicity. Additional research is necessary to explore the mechanisms underlying these changes and to understand the long-term impact of missed referrals and enrollments on military children.